Development of a Stability Control Method for the Aero-Train - Satoshi KIKUCHI; Fukuo OHTA; Takuma KATO; Tomomi ISHIKAWA; Yasuaki KOHAMA (Journal of Fluid Science and Technology, 2007)
Taking into account the seriousness of the greenhouse effect, drastic measures must be taken to prevent carbon dioxide emissions from transportation systems. In Japan, over 20% of the carbon dioxide is emitted from transportation systems. Aero-Train is a new zero-emission high-speed vehicle proposed by the authors. Aero-Train levitates aerodynamically using the wing-in-ground effect (WIG). In order to investigate the stability of Aero-Train, wind tunnel experiments of the front body section of a test run model of Aero-Train (ART002) and a levitating test run of ART002 using an improved control program were performed. The results showed that the front section of the body is unstable or is weakly stable in the direction of yawing and rolling. In the levitating test run of ART002, levitated running without surface contact was achieved inside the guide way. The amplitude of the roll angle oscillation was reduced by more than 50% compared to that of the previous control program. However, the vibration of the rolling remained.